2016
DOI: 10.6007/ijarbss/v6-i10/2363
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Intrinsic and Extrinsic Rewards on Employee Performance in Kapsara Tea Factory Company Trans Nzoia County Kenya

Abstract: The purpose of the study was to analyse the determinants of extrinsic and intrinsic rewards on employee performance. The specific objectives were: To examine the effect of employee Motivation on organizational Performance; to evaluate the effect of Employee Commitment on Organizational Performance; to determine the effect of employee training on organizational performance in Kapsara Company Kitale, Trans Nzoia County. Literature was reviewed based on the study objectives. The study was conceptualized on two ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
4
0
1
Order By: Relevance
“…In addition, the researcher added a few relevant models to draw the conceptual framework and development of hypotheses. Kilimo, Namusonge, and Makokha (2017) performed research on the relationship of extrinsic rewards on employee performance among 60 employees of Tea Factory Company Trans Nzoia County Kenya, the findings of the study concluded with clear proof that extrinsic rewards have a positive significant relationship with employee performance. Khan, Shahid, Nawab, and Wali (2013) conducted research about the impact of intrinsic rewards and extrinsic rewards on employee performance among 165 employees of the private bank sector of Pakistan, the result of the study found that extrinsic rewards positively influence employee performance.…”
Section: Theoretical Frameworkmentioning
confidence: 89%
“…In addition, the researcher added a few relevant models to draw the conceptual framework and development of hypotheses. Kilimo, Namusonge, and Makokha (2017) performed research on the relationship of extrinsic rewards on employee performance among 60 employees of Tea Factory Company Trans Nzoia County Kenya, the findings of the study concluded with clear proof that extrinsic rewards have a positive significant relationship with employee performance. Khan, Shahid, Nawab, and Wali (2013) conducted research about the impact of intrinsic rewards and extrinsic rewards on employee performance among 165 employees of the private bank sector of Pakistan, the result of the study found that extrinsic rewards positively influence employee performance.…”
Section: Theoretical Frameworkmentioning
confidence: 89%
“…Both financial and non-financial rewards promote employee commitment (Shalini, 2020). The existing literature suggests that non-financial rewards influence employees in developed countries, and financial rewards are more important in developing countries (Kilimo et al, 2016;Kokubun, 2017). The literature suggests that non-financial rewards have not the same impact on all employees (Lok & Crawford, 2004).…”
Section: Discussion and Conclusion Discussionmentioning
confidence: 99%
“…All three facets of commitment individually and collectively stimulate employee motivation. Most researchers suggest that affective commitment's impact on motivation is higher than normative and continuous commitment (Awino & Kipsang, 2020;Kilimo et al, 2016).…”
Section: Discussion and Conclusion Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ganjaran ekstrinsik adalah perkara yang berkaitan dengan luar kepada pekerjaan itu sendiri. Ia terdiri daripada unsur-unsur seperti gaji, faedah sampingan, keselamatan pekerjaan, promosi, ruang pejabat yang privasi, dan iklim sosial (Kilimo et al, 2016). Contoh lain termasuklah persaingan gaji, kenaikan gaji, bonus yang tertentu dan pampasan.…”
Section: Ganjaran Kerja (Ekstrinsik)unclassified